نموذج لأسلوب تعليمي معاصر في التعليم العالي - الحقيبة التعليمية - العزاوي, نجم (Université de M'sila, 2011)
We find in our present and our reality contemporary educational similarity in the methods of teaching the classical method lectures or traditional method of transmitting information in a formal way for a large or medium of information and concepts through the lecturer (teacher) that has the qualities to qualify display information and concepts in terms of, "dumping appropriate and attractive, which raises the interest of students, and can deliver information and ideas to students with ease and given time no more than one hour in all possibilities."